Combined molecular dynamics simulations and experimental studies of the removal of cationic dyes on the eco-friendly adsorbent of activated carbon decorated montmorillonite Mt@AC. Issue 8 (8th February 2023) - Ouachtak, Hassan; El Guerdaoui, Anouar; El Haouti, Rachid; Haounati, Redouane; Ighnih, Hamza; Toubi, Yahya; Alakhras, Fadi; Rehman, Rabia; Hafid, Naima; Addi, Abdelaziz Ait; Taha, Mohamed Labd
Abstract : Eco-friendly Mt@AC composite material was prepared and characterized for removal of cationic dyes from aqueous solutions. The Molecular dynamics simulation was applied for evaluating the adsorption mechanisms. Abstract : In recent years, the combination of experimental and theoretical study to explain adsorbate/adsorbent interactions has attracted the attention of researchers. In this context, this work aims to study the adsorption of two cationic dyes, namely methylene blue (MB) and crystal violet (CV), on a green adsorbent Montmorillonite@activated carbon (Mt@AC) composite and to explain the adsorption behavior of each dye by the molecular dynamics (MD) simulation method. The eco-friendly nanocomposite Mt@AC is synthesized and characterized by the analysis methods: XRD, FTIR, BET, TGA/DTA, SEM-EDS, EDS-mapping and zeta potential. The experimental results of adsorption equilibrium show that the adsorption of the two dyes is well suited to the Langmuir adsorption model. The maximum adsorption capacity of the two dyes reaches 801.7 mg g −1 for methylene blue and 1110.8 mg g −1 for crystal violet. The experimental kinetics data fit well with a pseudo-first order kinetic model for the two dyes with coefficient of determination R 2 close to unity, non-linear chi-square χ 2 close to zero and lower Root Mean Square Error RMSE ( R 2 → 1 and χ 2 → 0, RMSE lower). Molecular dynamic simulations are run to gain insights on the adsorption process. According to the RDF analysis and interaction energy calculations, the obtained results reveal a better affinity of the CV molecule with both the AC sheet and montmorillonite framework as compared with MB. This finding suggests that CV is adsorbed to a larger extent onto the nanocomposite material which is in good agreement with the adsorption isothermal experiment observations.